Lower Respiratory Tract Infection Trends in East and South-East Asia: In the Light of Economic and Health Care Development - Jelle J. Feddema PhD, MSc; Anne M. van der Geest PhD, MSc; Eric Claassen PhD; Linda H. M. van de Burgwal PhD (SAGE Publishing, 2021)
This study explored to what degree economic development and improvement of healthcare are associated with lower respiratory tract infection (LRTI) mortality. A correlation analysis between LRTI mortality and Gross Domestic Product (GDP) per capita, and the Health Access and Quality Index (HAQI), respectively was conducted for 15 countries in East and South-East Asia. The results revealed a dramatic decrease in LRTI mortality in total populations for lower-middle income (LMI) countries but at the same time an increase in upper-middle income (UMI) and high-income (HI) countries. A highly significant ( P  < .001) growth-dependent relationship between LRTI mortality and economic growth was observed. Improvements in HAQI were significantly associated with a decrease in LRTI mortality in LMI countries, but an increase in UMI and HI countries. The decline of LRTI mortality amongst children in LMI countries is an encouraging trend and efforts against LRTI must be continued, though not at the expense of preparing health systems for the growing burden.